School Tracks as Differential Learning Environments Moderate the Relationship Between Teaching Quality and Multidimensional Learning Goals in Mathematics - Schiepe-Tiska, Anja (Frontiers in Education, 2019)
Schools and teaching aim at fostering multidimensional learning goals. For attaining these goals, institutional effects such as school tracking as well as teaching quality play an important role and interact with each other. Using representative data from a class based German extension of the PISA 2012 study, the present study first investigated whether the factorial structure of three basic dimensions of teaching quality (cognitive activation, classroom management, and teacher support) in mathematics is comparable across high and low school tracks and tested whether tracks differed in students’ perception of mathematics teaching quality. Second, differences between school tracks in the relationship between teaching quality and multidimensional learning goals, namely mathematics competence, interest, and self-efficacy were examined. Results indicated that students in both school tracks distinguish between three dimensions of teaching quality and that the factorial structure is comparable across tracks. Students at higher school tracks report higher levels of discipline but lower levels of teacher support. No difference has been found for cognitive activation. In association with different learning goals, tracks show individual profiles. Mathematics competence is related to classroom discipline at the student level for lower school tracks and at the class level for higher school tracks. Mathematics interest is, at the student level, in both tracks associated with teacher support and discipline. In addition, in lower school tracks a cognitive activating learning environment is associated with more interest in mathematics. High levels of mathematics self-efficacy are in both school tracks reported by students who perceive their lessons as cognitive activating. In addition, high ability students who feel more supported by their math teachers report higher levels of self-efficacy. The results speak clearly for the assumption of school tracks as differential learning environments. They ask for a differentiated view of teaching quality and its impact on reaching multidimensional learning goals in order to meet students’ needs specifically and deal with increasing classroom heterogeneity.